2021
DOI: 10.1002/1878-0261.12975
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide from the commensal microbiota of the breast enhances cancer growth: role of S100A7 and TLR4

Abstract: The role of commensal bacterial microbiota in the pathogenesis of human malignancies has been a research field of incomparable progress in recent years. Although breast tissue is commonly assumed to be sterile, recent studies suggest that human breast tissue may contain a bacterial microbiota. In this study, we used an immune-competent orthotopic breast cancer mouse model to explore the existence of a unique and independent bacterial microbiota in breast tumors. We observed some similarities in breast cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…LPS, which is a cell wall component of Gram-negative bacteria, was widely used to induce mastitis model in vivo and in vitro ( 42 45 ). It is reported that LPS from the commensal microbiota of the human breast induced the expression of S100A7 in breast cancer cells ( 46 ). Consistent with previous reports, after treatment with LPS, the inflammatory response-related factors, including IL-6, IL-1β, and TNF-α, were obviously increased.…”
Section: Discussionmentioning
confidence: 99%
“…LPS, which is a cell wall component of Gram-negative bacteria, was widely used to induce mastitis model in vivo and in vitro ( 42 45 ). It is reported that LPS from the commensal microbiota of the human breast induced the expression of S100A7 in breast cancer cells ( 46 ). Consistent with previous reports, after treatment with LPS, the inflammatory response-related factors, including IL-6, IL-1β, and TNF-α, were obviously increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study demonstrated that the breast tumor microbiota was enriched with Gram-negative bacteria producing LPS. In vitro LPS treatment was shown to upregulate S100A7 expression in breast cancer cells, resulting in the upregulation of RAGE expression along with a reduced TLR4 expression that may contribute to tumor growth progression (115).…”
Section: Role Of Lipopolysaccharide In the Interplay Between Microbio...mentioning
confidence: 99%
“…Notably, among multiple cancers, a particularly rich and diverse microbiome has been observed in BC [ 33 ]. Wilkie et al revealed that BC commensal microbiota is distinctly composed of Gram-negative bacteria and highlighted the role of bacterial components in BC development [ 34 ]. As one of the recently identified BC-related microbes, F. nucleatum has gained the most attention.…”
Section: Discussionmentioning
confidence: 99%